Efisiensi Listrik pada Rumah Pintar berdasarkan User Habit menggunakan Fuzzy Logic dari Kontrol Lampu Berbasis Android - Yanto, Sandi; Hariyanto, Nurman; Hidayati, Awanis; Pratama, Aditya (Program Studi Manajemen Informatika, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia, 2025)
Electricity wastage, particularly in the industrial and household sectors, remains a significant issue in Indonesia. This is primarily caused by the lack of public awareness regarding efficient energy usage, which negatively impacts both the economy and the environment. This study aims to develop a dynamic and adaptive Android-based lighting control system using the Fuzzy Logic method to help reduce electricity consumption based on user habits. The Fuzzy Logic algorithm processes lamp usage duration data as input to generate automatic recommendations or notifications for optimal switch-off times. Testing was conducted through hardware implementation, Android application trials, and validation of the Fuzzy Logic method using usage duration parameters. Results showed energy efficiency across five lighting points, with average duration reductions ranging from 45.93 to 55.73 minutes—equivalent to 6%–7% savings per lamp. The system successfully reduces manual intervention, provides reminder notifications, and enhances the comfort of smart home occupants. These findings demonstrate that integrating Fuzzy Logic into habit-based lighting control is effective in minimizing electricity waste while intelligently adapting to daily usage patterns.